Evaporation of water: evaporation rate and collective effects. (9th June 2016) - Carrier, Odile; Shahidzadeh-Bonn, Noushine; Zargar, Rojman; Aytouna, Mounir; Habibi, Mehdi; Eggers, Jens; Bonn, Daniel
Abstract : We study the evaporation rate from single drops as well as collections of drops on a solid substrate, both experimentally and theoretically. For a single isolated drop of water, in general the evaporative flux is limited by diffusion of water through the air, leading to an evaporation rate that is proportional to the linear dimension of the drop. Here, we test the limitations of this scaling law for several small drops and for very large drops. We find that both for simple arrangements of drops, as well as for complex drop size distributions found in sprays, cooperative effects between drops are significant. For large drops, we find that the onset of convection introduces a length scale of approximately 20 mm in radius, below which linear scaling is found. Above this length scale, the evaporation rate is proportional to the surface area.